STATUS PERKEMBANGAN SEPEDA LISTRIK DAN MOTOR LISTRIK DI INDONESIA - I Pt Agus Surya Adi P; I Nyoman Satya Kumara; I Gusti Agung Pt Raka Agung (Program Studi Teknik Elektro UNUD, 2021)
The development of electric vehicles in Indonesia began in 1997 by the IndonesianInstitute of Sciences (LIPI) but since 2013 has slowed down. Presidential Regulation 55/2019strengthens the development of electric vehicles in Indonesia which followed by severalsupporting regulations. Currently, the development of electric vehicles, both in terms of researchand industry or commercial products, is getting better. This paper reviews the current status ofelectric bicycles and electric motorcycles in Indonesia which are commercially available. Theresearch was conducted by through online survey during 2020-2021 which produced adatabase of electric bicycles/motorcycles. Currently, there are 64 electric bicycles and 44electric motorcycles. These vehicles use either two or three wheels with electric drive capacitybetween 180 W to 4200 W. The most common electric motor used is BLDC at 87%. The electricbike/motorcycle has speed ranges between 20 km/h to 70 km/h with battery capacity of 5,2 Ahto 70 Ah with milage ranging from 15 km to 200 km. The information presented will helpstakeholders to get a quick overview of the development of electric bicycles/motorcycles in thecountry and serves as benchmark for developing electric bicycles or motor to meet domesticneeds.